Analysis of metallographic structure and hardness of magnesium alloy area using friction stir welding. (16th September 2019) - Hongfeng, Wang; Dunwen, Zuo; Shengrong, Liu; Weiwei, Song
The present work envisages the friction stir welding of AZ40 M magnesium alloy to analyze the influence of different process parameters (rotation speeds: 600, 800, and 1000 r/min; feed speeds: 100, 120, and 150 mm/min) on the metallographic structure at different locations in the weld zone. The welded regularity, analysis of the distribution law of the weld surface, and section hardness value (HV) were obtained under different welding process parameters. Our results show that, when the current feed rate was constant, the grain size of the weld nugget increased with an increase in the rotation speed. When the rotation speed was constant, the grain size of the weld nugget area decreased initially, which subsequently increased with an increase in the advance speed. When the rotation speed was 600 r/min and the feed speed was 120 mm/min, the nugget region grain was uniform, fine, and exhibited a highest HV.